Kinerja Aparatur Pemerintah Desa dalam Pelayanan Administrasi Kependudukan (Studi di Desa Bululawang Kecamatan Bululawang Kabupaten Malang) - Wicaksono, Tomy Hadi (Jurnal Administrasi Publik, 2015)
Abstract: Apparatus Performance Village Government in the Population Administration Services (Studies in Desa Bululawang, Kecamatan Bululawang, Kabupaten Malang). This study describes the performance of the government apparatus Bululawang Village in providing services to rural and neighbou outlining the quality of existing services in the implementation of the services carried out by government officials Bululawang village. Bululawang village itself has a population of events is quite high and included in the urban rural classification is based on the classification determined by the BPS (Badan Pusat Statistik). Thus the performance and quality of service Bululawang village government officials should be more qualified than the other village. It can be a problem that comes out is about the performance of government officials Bululawang village, and quality of service in the implementation of government services in the village of Bululawang. This study showed that the village government apparatus Bululawang performance has been quite good but the quality of service needs to be scaled back. So it becomes useless if the apparatus has a good performance, but the quality of service still has shortcomings. Keywords: apparatus, performance, service quality Abstrak: Kinerja Aparatur Pemerintah Desa dalam Pelayanan Administrasi Kependudukan (Studi di Desa Bululawang Kecamatan Bululawang Kabupaten Malang). Kinerja aparatur pemerintah desa dan juga kualitas pelayanan yang ada dalam pelaksanaan pelayanan adalah kunci pokok dalam penelitian ini. Desa bululawang adalah desa mempunyai peristiwa kependudukan yang cukup tinggi dan sesuai klasifikasi BPS, desa bululawang masuk dalam kategori desa perkotaan. Oleh karena itu, menjadi menarik bahwa dalam penelitian ini mengukur tentang kinerja maupun kualitas pelayanan aparatur pemerintah desa Bululawang. Maka dapat ditarik sepasang permasalahan yang keluar yaitu mengenai kinerja aparatur pemerintah desa Bululawang, dan kualitas pelayanan dalam pelaksanaan layanan di pemerintah Desa Bululawang. Penelitian ini menunjukkan hasil bahwa aparatur pemerintah desa bululawang berkinerja sudah cukup baik namun kualitas pelayanan perlu ditingkatkan kembali. Sehingga menjadi tidak sia-sia apabila aparatur mempunyai kinerja yang baik namun kualitas pelayanan tetap memiliki kekurangan. Â  Kata kunci: kinerja, aparatur, kualitas pelayanan.